Irrigation potential and investment return in Kenya - You, Liangzhi; Xie, Hua; Wood-Sichra, Ulrike; Guo, Zhe; Wang, L. (Elsevier, 2014)
The potential for irrigation investments in Kenya is highly dependent upon geographical, agronomic and economic factors that need to be taken into account when assessing the long-term viability and sustainability of planned projects. This study analyzed large dam-based and small-scale irrigation potential and investment needs for Kenya based on agronomic, hydrological, and economic factors. The analysis of small-scale irrigation expansion shows that the potential for investment in small-scale projects in Kenya ranges from 54,000 ha to 241,000 hectares, with an internal rate of return from 17% to 32%. For the dam-based investment analysis, under low-cost assumption, 58 dams of 73 are profitable (IRR > 0). At high cost level, the number is 52. If we raise the IRR cutoff value to 12%, 32 dams are economically feasible. We showed that there is considerable scope for the expansion of both dam-based and small-scale irrigation in Kenya, and we also provided a strategic prioritization for investments in irrigation schemes and projects.